Effect of glyphosate contamination on surface charge change and nutrients of degraded Inceptisols ameliorated with sub-bituminous coal - Herviyanti, Herviyanti; Maulana, Amsar; Harianti, Mimien; Lita, Arestha Leo; Prasetyo, Teguh Budi; Juwita, Pitri; Kurnianto, Reza Tri; Yasin, Syafrimen (Brawijaya University, 2024)
The widespread use of glyphosate to eradicate weeds in agricultural areas has the potential for contamination and residues in the soil that must be carefully considered. This study aimed to elucidate the effect of glyphosate contamination on the chemical properties of an Inceptisol ameliorated with sub-bituminous coal. This study used a completely randomized design with three treatments and three replications, namely A = control (soil with no glyphosate and sub-bituminous coal), B = 5 kg soil + 100 mg glyphosate L-1, and C = 5 kg soil + 40 t sub-bituminous coal ha-1 + 100 mg glyphosate L-1. The results showed that glyphosate contamination significantly affected pH, electrical conductivity (EC), mineral and organic matter (OM) composition, cation exchange capacity (CEC), organic carbon (OC), total N, and available P of an Inceptisol ameliorated with sub-bituminous coal. The application of 40 t sub-bituminous coal ha-1 as an alternative ameliorant improved pH H2O by 0.30, EC by 0.05 dS m-1, OM by 1.03%, CEC by 18.08 cmol(+) kg-1, OC by 1.16%, total N by 0.20% and available P by 5.47 ppm of the soil compared to the control. The residual glyphosate concentration in the soil ameliorated with sub-bituminous coal was 0.04 mg kg-1 compared to the initial glyphosate concentration of 100 mg L-1. The correlation between glyphosate residue had no significant relationship with the chemical properties of an Inceptisol ameliorated with sub-bituminous coal.